Urinary PH and crystals association with bacterial isolates in patients with urinary tract infection - Hiro M. Obaid; Shawbow A. Juma (Tikrit Journal of Pure Science, 2023)
Urinary Tract Infection (UTI) is among the most community infections worldwide. Host factors such as patients age and gender may influence the prevalence of the infection. In this study a total of 186 urine samples from patients) 1–79 years( whom attended Azady Teaching Hospital at Kirkuk province, for UTIs disorders, were examined microscopically and  cultured on suitable medias .The age group which were significantly more infected was 20 – 40 years with rate 21.1-34.9 %. The most common bacteria was Escherichia coli with rate of 60.3, 42.3% for each of females and males respectively. Followed by Staphylococcus aureus and Pseudomonas aeruginosa. Among 13 antibiotics used for sensitivity test S. aureus and K. pneumonia were more resistance comparing with other bacteria, they were resistant to 6 antibiotics, followed by Streptococcus sp. which was resistant for five antibiotics. Proteus mirabilis was resistant for four antibiotics, each of E. coli, P. aeruginosa and Serratia sp. were resistant for only three antibiotics. The majority of isolates were sensitive to tobramycin ceftizoxime and ntrofurantion, followed by chloramphenicol and ampcillin.whereas, high level resistance was seen to augmentin amoxicillin and nalidixic acid.